2021
DOI: 10.3390/pharmaceutics13030338
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Alginate/Carboxymethyl Chitosan/Aminated Chitosan Microcapsules for Efficient Encapsulation and Delivery of Diclofenac Sodium

Abstract: To develop an effective pH-sensitive drug carrier, alginate (Alg), carboxymethyl chitosan (CMCs), and aminated chitosan (AmCs) derivatives were employed in this study. A simple ionic gelation technique was employed to formulate Alg-CMCs@AmCs dual polyelectrolyte complexes (PECs) microcapsules as a pH-sensitive carrier for efficient encapsulation and release of diclofenac sodium (DS) drug. The developed microcapsules were characterized by Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…SA is an environmentally friendly biopolymer because of its biodegradability and nontoxic nature. 34 , 35 Based on these criteria, SA has drawn special attention in wastewater treatment applications as a premium encapsulating material owing to its notable advantages including strong gelation, high chemical stability, and biocompatibility. 36 , 37 In addition, the backbone chain of SA possesses plentiful functional groups such as hydroxyl and carboxyl groups that reinforce the chelating ability toward the cationic pollutants whether in heavy metals or dyes.…”
Section: Introductionmentioning
confidence: 99%
“…SA is an environmentally friendly biopolymer because of its biodegradability and nontoxic nature. 34 , 35 Based on these criteria, SA has drawn special attention in wastewater treatment applications as a premium encapsulating material owing to its notable advantages including strong gelation, high chemical stability, and biocompatibility. 36 , 37 In addition, the backbone chain of SA possesses plentiful functional groups such as hydroxyl and carboxyl groups that reinforce the chelating ability toward the cationic pollutants whether in heavy metals or dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (Cs) is a cationic polysaccharide polymer that is easily obtained via N-deacetylation of chitin, the essential component of the exoskeleton of crustaceans like shrimp, fungi, crab and insects 22 , 23 . Owing to its unparalleled merits such as biocompatibility, polyelectrolyte properties, recyclability, hydrophilicity, biodegradability and adhesion properties, chitosan has a significant deal of interest as an efficient cationic adsorbent for removal of heavy metals, pharmaceutical pollutants and organic dyes from their aqueous solutions 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CS has the ability to accelerate wound healing not only through its basic antimicrobial characteristics but also by the benefit of its aptitude to deliver various antimicrobial agents and growth factors to various types of wounds [ 24 ]. Additionally, aminated chitosan (aminochitosan; AmCs) is an interesting chitosan derivative that has been developed by the authors’ previous work with extra amine groups [ 25 ]. Compared with neat CS biopolymer, AMCS derivative has demonstrated better biological properties, including biocompatibility and biodegradability [ 26 ].…”
Section: Introductionmentioning
confidence: 99%